Treatment Resistance in Severe Asthma Patients With a Combination of High Fraction of Exhaled Nitric Oxide and Low Blood Eosinophil Counts - Hoshino, Yuki; Soma, Tomoyuki; Uchida, Yoshitaka; Shiko, Yuki; Nakagome, Kazuyuki; Nagata, Makoto (Frontiers in Pharmacology, 2022)
Background Combining fraction of exhaled nitric oxide (FeNO) and blood eosinophil count (B-EOS) may be a useful strategy for administration of type of biologics such as anti-IgE or anti-IL-5 biologics to severe asthmatics with type 2 inflammation and is important to be elucidated considering the increasing use of biologics. Methods This cross-sectional study analyzed clinical data from114 adult patients with severe asthma, who were treated at Saitama Medical University Hospital. Eligible patients were stratified into four subgroups defined by thresholds of FeNO and blood eosinophil (B-EOS) counts to detect sputum eosinophilia, using receiver operating characteristic curve (ROC) analysis. Seventy-five patients with optimal samples were stratified into four subtypes defined by thresholds of sputum eosinophilia and neutrophilia. Clinical characteristics, pattern of biologics, and distribution of sputum subtypes were analyzed in the stratified subclasses according to FeNO and B-EOS thresholds. The acute asthma exacerbation (AE)-free time of the FeNO/B-EOS subgroups and any biologics treatment including anti-IgE or anti-IL-5 biologics were examined using the Kaplan–Meier method. hazard ratio (HR) for acute AE-free time were examined using the Cox proportional hazard model. Results The optimal cut-off values for prediction of sputum eosinophilia were defined as ≥2.7%, wherein FeNO ≥ 27 ppb and B-EOS ≥ 265/µL, were respectively considered. The high FeNO subgroups showed significant high total IgE, compared with the low FeNO. The high FeNO/high B-EOS and the high FeNO/low B-EOS subgroup showed the largest prevalence of mepolizumab and benralizumab use among the other FeNO/B-EOS, respectively. The high FeNO/low B-EOS showed the largest frequency of AEs, low HR for and the shortest AE-free time, compared with the other FeNO/B-EOS. The sputum eosinophil-predominant subtype was the great majority in the high FeNO/high B-EOS. A diverse distribution of sputum leukocyte-predominant subtype was observed in the other FeNO/B-EOS. The subsequent AE-free time and its HR were comparable among the biologics use groups. Conclusion This strategy of classifying based on combination of FeNO and B-EOS proposes a particular refractory type 2 severe asthma and underlying airway inflammation, as a feasible trait for optimal biologics use.